2012
DOI: 10.1115/1.4006537
|View full text |Cite
|
Sign up to set email alerts
|

Aerothermal Performance of a Cooled Winglet at Engine Representative Mach and Reynolds Numbers

Abstract: This paper presents an experimental investigation of the aerothermal performance of a cooled winglet tip under transonic conditions (exit Mach number of 1.0, and an exit Reynolds number of 1.27 × 106, based on axial chord). Spatially resolved heat transfer data and film cooling effectiveness data are obtained using the transient infrared thermography technique in the Oxford High-Speed Linear Cascade test facility. Aerodynamic loss data are obtained by traversing a specially made and calibrated three-hole press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Squealer tips (e.g., see Booth et al [1] and Ameri et al [3]) are commonly used to both reduce leakage and reduce the contact area if rubbing occurs. Winglets as described by Coull et al [4], Zhou et al [5], and O'Dowd et al [6] provide another means to reduce leakage and can be used in combination with squealer cavities. Shrouded airfoils are another alternative.…”
Section: Introductionmentioning
confidence: 99%
“…Squealer tips (e.g., see Booth et al [1] and Ameri et al [3]) are commonly used to both reduce leakage and reduce the contact area if rubbing occurs. Winglets as described by Coull et al [4], Zhou et al [5], and O'Dowd et al [6] provide another means to reduce leakage and can be used in combination with squealer cavities. Shrouded airfoils are another alternative.…”
Section: Introductionmentioning
confidence: 99%
“…O'Dowd et al [31] concluded that the turbine blade tip heat transfer is greatly influenced by the shock wave structure inside the tip gap. O'Dowd et al [32] showed that tip Nusselt number increases with coolant injection, and it also increases with increase tip clearance. Coull et al [33] investigated the design of winglet tips for an unshrouded high pressure turbine blade, considering aerodynamic and thermal performance simultaneously.…”
Section: Introductionmentioning
confidence: 97%
“…Only the suction-side squealer with constant width winglet showed heat transfer reduction by 5.5%. O'Dowd et al [31,32] reported transonic heat transfer over a winglet tip without and with cooling, respectively. It has a centerline gutter and a small recessed cavity on the pressure-side overhang.…”
Section: Introductionmentioning
confidence: 99%
“…O'Dowd et al [17] concluded that the turbine blade tip heat transfer is greatly influenced by the shock wave structure inside the tip gap. O'Dowd et al [18] showed that tip Nusselt number increases with coolant injection, and it also increases with increase tip clearance. Coull et al [19] investigated the designs of winglet tips for unshrouded high pressure turbine blade, considering aerodynamic and thermal performance simultaneously.…”
Section: Introductionmentioning
confidence: 97%
“…Saha et al [16] carried out numerical simulations to explore the effect of a pressure-side winglet on flow and heat transfer over a plane, cavity squealer, and suction-side squealer tips. O'Dowd et al [17,18] reported transonic heat transfer over a winglet tip without and with cooling, respectively. It has not only a centerline gutter but also a small recessed cavity on its pressure-side overhang.…”
Section: Introductionmentioning
confidence: 99%